The Influence of Work Motivation, Work Discipline, Work Experience and Capabilities on Employee Performance at the Brastagi Supermarket Rantau Prapat Supermarket - Cempaka Andriyani; Sumitro Sumitro; Meisa Fitri Nasution (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the effect of work motivation, work discipline, work experience and ability on employee performance at the Brastagi Supermarket Rantau Prapat..This type of research is quantitative, and the place of implementation of the research is at the Brastagi Supermarket Rantau Prapat Supermarket. Data collection techniques used in this study were observation, documentation and questionnaires using a Likert scale.The population contained in this study are employeesSupermarket Brastagi Supermarket Rantau Prapatwhich totaled 53 people. Samples were taken using a saturated sampling technique. Therefore,then all populations become the object of research, namely as many as 53 people.The results showed that work motivation, work discipline, work experience and abilitysimultaneously positive and significant effect onemployee performance at the Brastagi Supermarket Rantau Prapat. The R Square value from the analysis of the coefficient of determination is 0.749, meaning that employee performance can be explained by work motivation variables,work discipline,work experienceandability of 74.9%, while the remaining 25.1% can be explained by other variables not examined in this study.